Diet quality and nutritional status of HIV-exposed children aged between 6 and 18 months in the Greater Accra Region of Ghana - Folson, Gloria K.; Bannerman, Boateng; Asante, Millicent; Tokor, Grace Siba; Ador, Gabriel; Atadze, Vicentia; Puplampu, Peter; Dame, Joycelyn Assimeng; Neizer, Margaret; Yamauchi, Futoshi (Frontiers in Sustainable Food Systems, 2024)
Introduction HIV-exposed children, even when uninfected, have a greater risk of malnutrition than unexposed counterparts. WHO guidelines recommend children aged 6–23 months be fed a variety of foods to meet nutrient requirements. This study aimed to determine infant and young child feeding (IYCF) practices among HIV-exposed children under 2 years old enrolled in a dietary intervention and to explore correlates of the IYCF indicators and associations between IYCF and nutritional status. Methodology Six hundred and eighty mother–child pairs were recruited from 19 health facilities from the Greater Accra Region. The sociodemographic data, anthropometry, hemoglobin, and dietary intake were recorded. Results Ninety-five percent of HIV-positive mothers breastfed their babies, and 53% initiated breastfeeding in a timely manner. Around one in five mothers (21%) introduced liquids other than breastmilk to their children within the first 2 days of birth, and only around one in four children (26%) aged 12–23 months had received breast milk on the day before assessment. Ninety-three percent of babies between 6 and 8 months had been introduced to solid, semi-solid, or soft foods. Eighteen percent of children reached the threshold for Minimum Dietary Diversity (MDD) by eating from over five of eight food groups. Fifty-four percent received Minimum Meal Frequency (MMF), eating between 2 and 4 meals in a day. Eleven percent received the Minimum Acceptable Diet (MAD). Thirty-two percent were anemic. Underweight and stunting were 12 and 11%, respectively. Children of mothers aged 31–40 years were more likely to meet the MDD and MAD [OR = 2.8, 95%CI (1.185, 6.519), p < 0.05 and OR = 2.8, 95%CI (1.256, 6.279), p < 0.05] compared to children of mothers aged 30 years or less or aged above 40 years. Children from households earning more than GHS 500 were more likely to meet MMF than those from households earning less. No associations were found between IYCF and nutritional status. Conclusion Findings highlight the need for nutrition programs to educate HIV-exposed children’s caregivers on optimal feeding practices. The importance of continued breastfeeding and dietary diversity needs to be highlighted. Affordable, iron-rich foods should be promoted. Special attention should be paid to younger, less educated, and lower socioeconomic status mothers.